PENGARUH TEKANAN KERJA, BEBAN KERJA DAN LINGKUNGAN KERJA TERHADAP INTENSI TURNOVER: PERAN MEDIASI KEPUASAN KERJA - Prahyudi Apriyanto; Siswoyo Haryono (Universitas Sarjanawiyata Tamansiswa, 2020)
Turnover Intention in the present study was defined as a situation where employee leaves company due to disturbance in operation, team work dynamics, and unit performance of PT. Patria Migas. This study aims to determine the direct effects of work stress, workload, work environment on turnover intentions, and the effects of work stress, workload, work environment on turnover through job satisfaction as a mediating variable. The subjects in this study are employees of PT. Patria Migas, with a total of 48 respondents. The model in the study was tested using Structural Equation Model (SEM) data analysis technique with Partial Least Square (PLS) and using software SmartPLS 3.0. The result of the study indicates positive and significant effects both directly of work stress, workload, and work environment on turnover intentions, and mediation of work stress, workload, and work environment turnover intentions mediated by job satisfaction. This study is expected to add insight on turnover intentions and variables such as work stress, workload, work environment an job satisfaction which can create turnover intentions.Keywords: work stress, workload, work environment, job satisfaction, and turnover intentions.